The Museum as a Cinematic Space: The Display of Moving Images in History Museums (Cinéma & Cie. Film and Media Studies Journal, 2015)
In the last decades moving images have become a common feature not only in art or film museums, but also in a wide range of institutions devoted to the conservation and transmission of memory. This paper focuses on the role of audio-visuals in the exhibition design of contemporary history and memory museums. Starting from a classification of the different kinds of audio-visuals used in these institutions, I will analyze not only “literal” presence of audio-visuals in exhibitions, but also the ways in which the museum dispositive can incorporate elements of the cinematic dispositive. I will show how, on the one hand, exhibitions can be structured according to cinematic principles such as montage and sequentiality and, on the other hand, how the configuration of museums space can be deeply influenced by the “classic” cinematic dispositive and its components (screen, dark room, projection, sitting spectator).